Anthropogenic stressors impact fish sensory development and survival via thyroid disruption - Besson, Marc; Feeney, William E.; Moniz, Isadora; François, Loïc; Brooker, Rohan M.; Holzer, Guillaume; Metian, Marc; Roux, Natacha; Laudet, Vincent; Lecchini, David (Nature communications, 2020)
Larval metamorphosis and recruitment represent critical life-history transitions for most teleost fishes. While the detrimental effects of anthropogenic stressors on the behavior and survival of recruiting fishes are well-documented, the physiological mechanisms that underpin these patterns remain unclear. Here, we use pharmacological treatments to highlight the role that thyroid hormones (TH) play in sensory development and determining anti-predator responses in metamorphosing convict surgeonfish, Acanthurus triostegus . We then show that high doses of a physical stressor (increased temperature of +3 °C) and a chemical stressor (the pesticide chlorpyrifos at 30 µg L −1 ) induced similar defects by decreasing fish TH levels and affecting their sensory development. Stressor-exposed fish experienced higher predation; however, their ability to avoid predation improved when they received supplemental TH. Our results highlight that two different anthropogenic stressors can affect critical developmental and ecological transitions via the same physiological pathway. This finding provides a unifying mechanism to explain past results and underlines the profound threat anthropogenic stressors pose to fish communities. Anthropogenic stressors affect many aspects of marine organismal health. Here, the authors expose surgeonfish to temperature and pesticide stressors and show that the stressors, separately and in combination, have adverse effects on thyroid signaling, which disrupts several sensory systems and important predation defenses.